BUREAUCRATIC REFORM IN HEALTH SERVICES: 112 CALL CENTER PROGRAM IN PAREPARE CITY - Ahmda, Srifatmawati; Azizi, Muhammad; Yusriadi, Yusriadi; Umar, Akmal; Sahid, Abdul (Universitas Medan Area, 2020)
Bureaucratic reform is an effort to renew the system of governance. One form of bureaucratic reform is health services as an effort to maintain and improve health. The type of research used was qualitative, the research location in Parepare City, informants in the study were eight people, namely four service users and four service providers, data explaining techniques with observation, interviews, and documentation. The results of the 112 Call Center program in Parepare City show that the implementation of the application has well implemented, innovation in the process of providing integrated health services to the community offers new ways of service, easy access to services by calling directly to number 112 with 24-hour service for seven days. The concept in this program has touched the people of Parepare City with continuous health services and is easily accessible to all levels of society